ANALISIS MINAT BACA SISWA MELALUI GERAKAN LITERASI KELAS V SD NEGERI KENDAL GONDANG KABUPATEN TULUNGAGUNG - Regita Cahyani, Putri Avida; Devi Asriyanti, Frita (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Literacy activities in Indonesia were announced by the government in 2016. School literacy can be defined asknowledge, understanding and skills that students canlearn at school. This study aims to determine students' interest in reading through the fifth grade school literacy movement at SD Negeri Kendal Gondang, Tulungagung Regency. By using qualitative methods and data collection techniques in the form ofinterviews, observation and documentation, the research results show that the school literacy movement carried out in class V of SD Negeri Kendal Gondang consists of three stages, namely thehabituation, development and assessment orevaluation stages, all of which require support. allschool members, including parents, to support the implementation of a school literacy movement program that is effective and able to increase interest in reading well. The reading interest of fifth grade students at Kendal Gondang State Elementary School is classified as moderate. For this reason, the school is working on a literacy movement with various forms of activitiessuch as spending time reading or getting children usedto reading 15 minutes before the start of learning,forming a literacy corner, making wall magazines andholding various activities oriented towards increasingstudents' interest in reading.